1997
DOI: 10.1097/00000478-199705000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of Cowper's Glands on Prostate Needle Biopsy

Abstract: The presence of normal anatomic structures may be a source of confusion to the pathologist examining prostatic needle biopsies. The morphologic features of Cowper's (bulbourethral) glands incidentally biopsied during transrectal sampling of the prostate have not been described. We reviewed seven cases of Cowper's glands found in prostatic core biopsy specimens. Sections containing Cowper's glands were stained with hematoxylin-eosin, mucicarmine, periodic acid-Schiff's-digest (PAS-D), and antibodies directed at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(14 citation statements)
references
References 8 publications
0
14
0
Order By: Relevance
“…Furthermore, basal cells of Cowper's glands may not express keratin 34b-E12, 86 although this has been disputed. 87 Rare (0.2%) cases of adenocarcinoma have been reported that express keratin 34b-E12, including foci of metastatic high-grade adenocarcinoma; these cases did not appear phenotypically to be basal cell/ adenoid cystic carcinoma. 88 Basal cell hyperplasia is a histologic mimic of cancer, and use of antikeratin 34b-E12 is recommended in any equivocal cases that include this lesion in the differential considerations.…”
Section: High-grade Pin Dg Bostwick and J Qianmentioning
confidence: 99%
“…Furthermore, basal cells of Cowper's glands may not express keratin 34b-E12, 86 although this has been disputed. 87 Rare (0.2%) cases of adenocarcinoma have been reported that express keratin 34b-E12, including foci of metastatic high-grade adenocarcinoma; these cases did not appear phenotypically to be basal cell/ adenoid cystic carcinoma. 88 Basal cell hyperplasia is a histologic mimic of cancer, and use of antikeratin 34b-E12 is recommended in any equivocal cases that include this lesion in the differential considerations.…”
Section: High-grade Pin Dg Bostwick and J Qianmentioning
confidence: 99%
“…20,21 They are rarely sampled in prostatic specimens. Cowper's glands have a lobular configuration with a central duct surrounded by tightly packed round acini composed of cells with abundant mucinous cytoplasm ( Figure 3).…”
Section: Cowper's Glandmentioning
confidence: 99%
“…Sometimes, skeletal muscle, typical of the apical region, is present in the periglandular stroma. Cowper's glands are rarely confused with small 20,21 The ductal cells exhibit high molecular weight keratin (34bE12) staining and in some cases attenuated cells around the periphery of the acini are also positive. 20 The latter cells may also exhibit smooth muscle actin positivity.…”
Section: Cowper's Glandmentioning
confidence: 99%
See 2 more Smart Citations